2000
DOI: 10.1177/004005990003200302
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Cultural Competence

Abstract: We developed this article as part of an Early Education Program for Children with Disabilities (EEPCD) demonstration project titled "71"ansitioning Young Culturally Diverse Children with Disabilities into Regular Education Classrooms." funded by the U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Additionally, fostering cultural competence can involve creating opportunities for educators to engage with diverse communities and cultures outside the classroom. This can include community outreach programs, service-learning initiatives, and partnerships with local organizations that promote diversity and social justice (Craig et al, 2000). These experiences enable educators to gain firsthand exposure to diverse perspectives and develop a deeper understanding of the communities they serve.…”
Section: Promoting Cultural Competence Among Educatorsmentioning
confidence: 99%
“…Additionally, fostering cultural competence can involve creating opportunities for educators to engage with diverse communities and cultures outside the classroom. This can include community outreach programs, service-learning initiatives, and partnerships with local organizations that promote diversity and social justice (Craig et al, 2000). These experiences enable educators to gain firsthand exposure to diverse perspectives and develop a deeper understanding of the communities they serve.…”
Section: Promoting Cultural Competence Among Educatorsmentioning
confidence: 99%
“…Cultural Competence as a Response to Structural Racism in Latino Substance Use and Access… DOI: http://dx.doi.org/10.5772/intechopen.103710 as compared to a wait-list control group [97,98]. Professions that have focused on including cultural competence in their work environment include business, social work, psychology, public relations, education, and health care [99][100][101][102].…”
Section: Cultural Competence Applied To Different Treatment Modalitiesmentioning
confidence: 99%
“…Teachers must respond optimally to student's diversity in order to comprehend the strengths and weaknesses of themselves and their students. This understanding can be reflected in the socio-cultural context of students and teachers (Craig et al, 2000;Emmanuel, 2003). Cultivating intercultural competence for prospective teachers aims at providing opportunities for reflection on how to educate students in diverse cultural situations and what material should students learn make them culturally responsible in society.…”
Section: Intercultural Competence For Music Teacher Educationmentioning
confidence: 99%
“…Emmanuel (2003) proposed the notion that teachers must face and test themselves against diversity; hence, they are able to get along with diverse learners as well. The ability of teachers to be intercultural is reflected on how they respond and see their students' diversity, both strengths and weaknesses, and vice versa (Craig et al, 2000;Emmanuel, 2003). In addition, Emmanuel's (2003) study revealed that most teacher candidates have good confidence about their personal backgrounds and life experiences; however, it actually affects the way they teach in class.…”
Section: Introductionmentioning
confidence: 99%